IMPROVING THE PERFORMANCE PROPERTIES OF AUTOMOTIVE PARTS BY FORMING WEAR-RESISTANT COATINGS - Posviatenko E. K.; Holovashchuk M. V. (World Science, 2022)
The work is devoted to solving the scientific and technical problem of ensuring the tribotechnical properties of car parts through the use of wearresistant coatings. The synthesis of the main types of wear of car parts and ways to improve their tribotechnical properties was carried out, which allowed to substantiate the feasibility of using wear-resistant coatings to restore and strengthen them.An urgent problem is the reasonable search and development of highly efficient, easy-to-use technologies for the restoration of parts to improve the performance of cars. Solving this problem requires the introduction into practice of strengthening and restoring car parts wear-resistant coatings. Summarizing the results of research on the main types of wear of car parts allowed us to conclude that they work in conditions where operating loads (pressure, temperature, environmental action, etc.) perceive mainly their surface layers, and therefore it is enough to restore not all parts but only worn surfaces by applying wear-resistant coatings.It has been proven that to improve the performance of car parts, it is important to choose the right simple and affordable ways to apply coatings that will increase their service life. It is substantiated that among the methods of applying wear-resistant coatings are the most common, cheapest and simplest methods of gas-thermal spraying, namely gas-flame spraying and electric arc spraying. Restoration and strengthening of car parts by applying wear-resistant coatings has solved the problem of providing their resource, which is not inferior to the resource of new parts.